DETERMINANTS OF SUCCESS IN VILLAGE FUND MANAGEMENT WITH GOAL COMMITMENT AS A MODERATION - Muhammad Salman; Iskandar Muda; Andri Soemitra; Yusrizal (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to examine the influence of Human Resources, Community Participation and Leadership Behavior on the Success of Village Fund Management with Goal Commitment as a Moderator. The respondents of this study were 54 people obtained through purposive sampling, from a total of 124 respondents who were village staff in 5 villages in Langsa Baro District, Langsa City. The number of respondents was obtained using the Slovin formula. The data obtained were analyzed using the Partial Least Square (PLS) analysis technique. The equation models analyzed were the outer model and inner model. The results showed that Community Participation, Leader Behavior and Goal Commitment had a significant effect on Village Fund Management, while Human Resource Quality did not have a significant effect on the Success of Village Fund Management. Furthermore, goal commitment was unable to moderate the influence of human resources, community participation and leader behavior on the success of village fund management.